Development, behaviour and autism in individuals with SMC1A variants. (8th October 2018) - Mulder, Paul A.; Huisman, Sylvia; Landlust, Annemiek M.; Moss, Jo; ,; Piening, Sigrid; Hennekam, Raoul C.; van Balkom, Ingrid D.C.
Abstract : Introduction: Development and behaviour in Cornelia de Lange Syndrome (CdLS), including autism characteristics, have been described infrequently stratified to genetic cause and only a few studies have considered behavioural characteristics in relation to developmental level. Here, we describe the behavioural phenotype in individuals with CdLS with SMC1A variants. Methods: We performed an international, interdisciplinary study on 51 individuals with SMC1A variants. Results of questionnaire studies are compared to those in individuals with Down Syndrome and with Autism Spectrum Disorder. Results on cognition and self‐injurious behaviour (SIB) are compared to those in individuals with CdLS caused by NIPBL variants. For Dutch participants with SMC1A variants we performed direct in‐person assessments of cognition, autism, and added an interview and questionnaire on adaptive behaviour and sensory processing. Results: Individuals with SMC1A variants show a higher cognitive level and less SIB than individuals with NIPBL variants. Individuals with SMC1A variants without classic CdLS phenotype but with a Rett‐like phenotype show more severe intellectual disability and more SIB compared to those with a CdLS phenotype. Autism is less present if outcomes in direct in‐person assessments are evaluated taking developmental level into account compared to results based on a questionnaire. Conclusions: Behaviour in individuals with CdLS should be evaluated taking genetic cause into account. Detailed interdisciplinary approaches are of clinical importance to inform tailored care and may eventually improve quality of life of patients and families.